2-Aminopyrimidinium nitrate - Cheng, X.L.; Gao, S.; Ng, S.W. (International Union of Crystallography, 2010)
In the title compound, C(4)H(6)N(3)(+) center dot NO(3)(-), the cation is coplanar with the anion (r.m.s. deviation = 0.048 angstrom), and links to the anion via an N-H center dot center dot center dot O hydrogen bond, forming an ion pair. In the crystal, adjacent ion pairs are further linked by N-H center dot center dot center dot O hydrogen bonds into linear chains running along the b axis.